Políticas de avaliação da Educação Superior da Universidade Federal do Tocantins UFT no contexto do SINAES: entre avaliadores e avaliados - Conceição, Maria de Fátima (2011)
In this work there is studied the politics of superior education of the Federal University of the Tocantins (UFT): between valuators and valued, whose objective is to rebuild the trajectory evaluative of the first cycle of institutional evaluation of the UFT, occurred in the year of 2006/2007 and to value the second process occurred in the year of 2009/2010, through an analysis that it makes possible to identify the conception/conceptions of evaluation that they subsidized the construction of the two processes and that they orientated the actions of the Own Commission of Evaluation (CPA) of the UFT, in the attempt of to perceive these evaluations like counterpoint to which it extols the National System of Evaluation of the Education Superior-SINAES. This is a case study carried out in the University Campus of Porto Nacional, of qualitative and quantitative character and is result of the partnership Professional Masters in Public Policy Evaluation (MAPP-UFC/UFT), being fitted inside the Line of Research Public Politics and Social Changes. The discussion that orientates all the work was anchored in great part by Sobrinho (2003), that it defends a democratic evaluation and also Cunha (2004), which works the factor emancipation x regulation inside the same phenomenon and, even, Lejano (2006), what defends the evaluation of public politics from an interpretative approach, valuing the vision and the participation in the evaluative process, when several actors wrapped in the politics, be usufructuary, technical and managers of the politics or social project. For the collection of data questionnaires were used, containing open and shut questions and also interviews. The questionnaires were answered by the teaching, learning and administrative-technical segments (valued) and the interviews only by valuators. Four empirical categories orientated the work: conception, participation, changes and results, and the collected data were analysed by the light of these categories for three segments. They pointed to a great fragility in the institutional evaluation of the UFT, especially in the category participation. This fact was punctuated enough by all the segments of the university, as valued as valuators. In case of the valuators, it emphasizes what, each one speaks of the place in which each one is and, with that, the more distant they remain themselves of the valued ones, the more also they are distanced of a democratic evaluation, having in mind what they incorporate the institutional speech. It is signaled what the fragility notes for the inquiry, it identifies the institutional evaluation of the UFT as being an evaluation more regulatory than emancipatory, as soon as the regulation disregards the actors of the process when deny they the participation and also what have voice and time.